Crescimento de Braquiária e Milho submetidos a diferentes concentrações de CO2 - Ferreira, Evander Alves; Cabral, Cássia Michelle; Fonseca, Darliana da Costa; Santos, José Barbosa dos (Revista Vozes dos Vales: Publicações Acadêmicas, 2023)
In the current context, where it is observed increase in CO2 concentration in the atmosphere coupled with the increase in temperature, which can make changes related to competitive ability of weeds and crops, where changes in growth, morphology and physiology of plants can be observed in such conditions. Given the above, the aim of this study to evaluate the effect of ambient CO2 level increase in the growth of plants braquiária and corn under competition. To this end it was mounted an experiment in a completely randomized design with four replications. To evaluate the effect on Brachiaria plants we used a factorial 3 x 4, the first factor represented by four concentrations of CO2 in growth chambers and three arrangements (Brachiaria cultivated alone braquiária + beggartick, braquiária + corn and pasture . + bean As to the assessment of maize plants the factorial was 3 x 3, the first factor represented by the three levels of CO2 in the growth chamber and the second factor corresponding to different arrangements: corn grown alone, corn + beggartick and corn + brachiaria. the increase in CO2 concentration influences evident form the growth of plants braquiária and corn, that is, higher CO2 levels promote the further growth of the crop and weed. Different CO2 levels environment also influence the competitive relationship between the species. at the concentrations of 420 and 860 ppm CO2 in the atmosphere the beggartick proved to be more competitive with brachiaria compared to beans and maize. In the higher concentration of CO2 was observed a tendency Brachiaria plants show similar behavior irrespective of the arrangement in which the weed was grown. Both beggartick as the plants of Brachiaria negatively affected the growth of maize plants, and the plants braquiaria affected growth more negatively corn compared with beggartick.
Keywords: Competitiveness; Weed; CO2 concentration